Synthesis and Curing of New Phenolic Resins Linking to Pyromellitdiimides - Abeer Khaleel (Journal of Global Pharma Technology, 2018)
In this work a series of new phenol-formaldehyde resins linking to pyromellitdiimide were synthesized via three steps in the first one a series of four N, N- bis ( hydroxy phenyl) pyromellitdiamic acids were synthesized by reaction of pyromelliticdianhydride with amino phenols. In the second step, the prepared diamic acids were dehydrated by fusion producing the corresponding pyromellitdiimides and these in turn were introduced in poly condensation reaction with formaldehyde producing the new target phenolic resins. Treatment of the prepared resins with benzoyl chloride afforded the corresponding modified resins. The newly synthesized and modified resins exhibit new properties that may serve many applications.Keywords: Pyromellitdiamic acids, Pyromellitdiimide, Phenolic resins, Amino phenols.